BACURAMIN KA’ SARUGA: A SUSTAINABLE PRESERVATION LOCAL PRINCIPLE IN KAPUAS HULU FOR KERUPUK BASAH AS GEOGRAPHICAL INDICATION - Purwanto, Purwanto (Faculty of Law Universitas Panca Bhakti, 2019)
Kerupuk Basah called temet by Kapuas Hulu Local Community was provided for home consumption long long time ago. But lately, it was spread throughout Kalimantan Barat Province, likely Pontianak, Mempawah and Sintang. The taste proved that Kerupuk Basah from Kapuas Hulu had some differences than others, including finer surface structure, stronger fish taste, and softer when pressed or chewed. The study used statute approach and method through indepth interview. The study found there were 3 (three) factors which influenced Kerupuk Basah taste from Kapuas Hulu, namely 1) natural factor (Toman and Belida fish were the main composition in making Kerupuk Basah were only find in upstream of Kapuas Hulu river); 2) human factor (Kerupuk Basah was initially processed by Kapuas Hulu local community in the past and had been preserved until now then made them had a special expertise and able to make good quality of Kerupuk Basah; 3) combination of natural and human factor (Belida and Toman fish lived there combined with local community ability made Kerupuk Basah had a good reputation and unique characteristic). All of those factors led Kerupuk Basah could be Kapuas Hulu Geographical Indication. Then, Bacuramin Ka?Saruga (Dayak principle as most of local people there) agreed choice by the community, local government and Small and Medium Enterprises in Kapuas Hulu.